If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 = 2(x + 8) Reorder the terms: 50 = 2(8 + x) 50 = (8 * 2 + x * 2) 50 = (16 + 2x) Solving 50 = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 50 + -2x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 50 + -2x = 16 + 0 50 + -2x = 16 Add '-50' to each side of the equation. 50 + -50 + -2x = 16 + -50 Combine like terms: 50 + -50 = 0 0 + -2x = 16 + -50 -2x = 16 + -50 Combine like terms: 16 + -50 = -34 -2x = -34 Divide each side by '-2'. x = 17 Simplifying x = 17
| -4-b=8 | | 6(6c-2)+8(1-5c)=-2c | | 2(4x+3)=6+2x(3) | | -7x-14=-28 | | 3n+2=27 | | 158-5x=5x+18 | | 2(x+3)=4(x+1) | | (2x+6)-(3x-4)+2x=-17 | | 2(2m-3)=-10(m+2) | | =2x^2+3x+16 | | -80-6x=28 | | -80+6x=28 | | 3m^2+7m+6= | | 4x^3=44 | | x^3-9x^2+6x-54= | | 125=5z | | -5(t+8)=5 | | -12x^2+26x=4 | | -3(5y-10)+2(3y+7)= | | -y(y^2-5)+4y^2(7y-4)= | | 39-19=4(x-7) | | -12x^2+26x=-4 | | -12x^2+26x=0 | | 7(5+7p)=-12+2p | | 4(3x-11)=-16 | | 23-11=2(x-7) | | 5x-24=90 | | q=t-1t^2 | | 2*18-(5-18)=13+2*18 | | (z-5)(z+4)=70 | | 34-2(2w+1)=5w-2 | | 10+3x=10-7x |